2009
DOI: 10.1074/jbc.m109.031849
|View full text |Cite
|
Sign up to set email alerts
|

p110 CUX1 Homeodomain Protein Stimulates Cell Migration and Invasion in Part through a Regulatory Cascade Culminating in the Repression of E-cadherin and Occludin

Abstract: In this study, we investigated the mechanism by which the CUX1 transcription factor can stimulate cell migration and invasion. The full-length p200 CUX1 had a weaker effect than the proteolytically processed p110 isoform; moreover, treatments that affect processing similarly impacted cell migration. We conclude that the stimulatory effect of p200 CUX1 is mediated in part, if not entirely, through the generation of p110 CUX1. We established a list of putative transcriptional targets with functions related to ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 53 publications
(65 reference statements)
4
75
1
Order By: Relevance
“…1 In agreement with these results, mouse embryonic fibroblasts (MEFs) from CUX1-knockout mice exhibited a defect in migration and invasion as compared to MEFs from wild type mice. 2 These observations were extended using an in vivo invasion assay. Indeed, pulmonary colonization after tail vein injection was reduced following stable expression of CUX1 shRNA in HT1080 and MDA-MB-231.…”
Section: Cell Migratory Properties Are Reduced In the Absence Of Cux1mentioning
confidence: 92%
See 2 more Smart Citations
“…1 In agreement with these results, mouse embryonic fibroblasts (MEFs) from CUX1-knockout mice exhibited a defect in migration and invasion as compared to MEFs from wild type mice. 2 These observations were extended using an in vivo invasion assay. Indeed, pulmonary colonization after tail vein injection was reduced following stable expression of CUX1 shRNA in HT1080 and MDA-MB-231.…”
Section: Cell Migratory Properties Are Reduced In the Absence Of Cux1mentioning
confidence: 92%
“…2 The defect was rescued completely by p110 CUX1, but only partially by p200 CUX1. Subsequent experiments showed that cell migration was stimulated by treatments that increase proteolytic processing of p200 CUX1 into p110 CUX1, whereas cell migration was decreased in the presence of a protease inhibitor that prevents the generation of p110 CUX1.…”
Section: Mefs Is Rescued By P110 Cux1 But Only Partially By the Fullmentioning
confidence: 98%
See 1 more Smart Citation
“…Using transcription and cellbased assays, a role for p110 CUX1 was shown in many cellular processes, notably in cell cycle progression and cell proliferation 21,22 , strengthening of the spindle assembly checkpoint 19 , establishment of a transcriptional programme that enables efficient DNA damage responses 23 , and cell migration and invasion 13,42 . In addition, from RNA interference (RNAi)-mediated knockdown and genetic inactivation, CUX1 was shown to be required for the resistance to apoptotic signals in pancreatic cancer cells 14 , the repression cytokine genes associated with M1 macrophages 43 , and dendrite branching and spine development in cortical neurons 34 .…”
Section: The Knudson Two-hit Modelmentioning
confidence: 99%
“…Many transcriptional targets and cellular functions of CUX1 readily suggest mechanisms by which increased p110 or p75 CUX1 expression might promote tumour development and progression, including acceleration of S phase entry 21,22,41,62,63 , stimulation of cell migration and invasion 13,42,[64][65][66] , resistance to apoptosis 14 , and promotion of bipolar mitosis in the presence of supernumerary centrosomes 19 (reviewed in REF. 67).…”
Section: Mechanisms Of Action In Cancermentioning
confidence: 99%